A escrita para percussão dos compositores do Grupo Música Nova: a busca pelo novo analisada a partir da notação - Stuani, Ricardo de Alcântara [UNESP] (2015)
This work aims to discuss aspects of percussion notation that were connected to a search for novelty in the music of the Brazilian composers Gilberto Mendes (1922), Rogério Duprat (1932 - 2006) e Willy Corrêa de Oliveira (1938), who signed the Manifesto Música Nova, in 1963. We believe that, according to the proposals contained in the Manifesto, in these scores we can find evidence of an attempt to renew musical aesthetics determined by the experimentalavant-gardethought, which can be examined on the basis of thecreation of new graphics, representing procedures of indeterminacy,improvisation, timbristic explorations and the incorporation of elements of poetic, theatrical and visual languages. The focus of the research is the Concerto para Tímpanos, Caixa e Percussão (Gilberto Mendes, 1991), Antinomies I (Rogério Duprat, 1962) and Memos (Willy Corrêa de Oliveira, 1977). In discussing the notation characteristics for percussion in these parts, we identified the positioning of the sixties avant-garde in its search for novelty that we also intend to evaluate through a trial of these three composers to incorporate typical Brazilian percussion instruments in their experimental music, in this case: the berimbau, the cuíca and the agogô, checking the notation problem for these instruments